Child protection in medicine - closing gaps in continuing education through e-learning. (13th November 2019) - Maier, A; Hoffmann, U; Fegert, J M
Abstract: Background: Child abuse is a major problem across Europe. The consequences are often serious and long-lasting disorders which, in addition to the individual burden, are extremely costly for the national health system. It is important to prevent or recognize child abuse at an early stage and to provide adequate help to those affected. Health professionals are privileged first contact persons for the victims. However, the WHO assumes that about 90% of cases of child abuse in medical institutions remain unknown. It is therefore important to train health professionals in this field. For this reason, in Germany an E-Learning course on child protection in medicine is currently being developed and evaluated. This article is intended to present the results of the accompanying evaluation of the E-Learning course. Methods: The accompanying evaluation collected and analyzed the graduates' opinion on the course, its contents and the topic of child protection in medicine in general. Knowledge and competence levels were surveyed before and after the course and evaluated with a t-test for related samples. Results: The evaluation of the course showed a high relevance of the topic of child protection in medicine and the rather low attention paid to the topic in the medical field. The course was, however, assessed very positively and the majority of graduates were already able to apply what they had learnt in their daily work. The pre-post design showed a significant increase in knowledge and skills as a result of the course. Conclusions: It turned out that the E-Learning course on child protection in medicine closes an existing gap in the continuing medical education system. The evaluation also shows a success of the program and thus a reduction of uncertainties in child protection procedures among health professionals. A corresponding E-Learning offer for other European countries should be considered in order to address the comprehensive problem of child abuse across the whole of Europe. Key messages: Too little attention is paid to child protection in the medical field. E-Learning can effectively train health professionals in child protection, has a wide reach and is flexible in use.